Physiological pharmacology. a comprehensive treatise - Root, Walter S. (Walter Stanton), 1902-1972; Hofmann, Frederick G. (Academic Press, 1967)
Physiological Pharmacology: A Comprehensive Treatise, Volume III: The Nervous System - Part C: Autonomic Nervous System Drugs focuses on the effects of drugs on the nervous system, including cardiovascular effects and metabolism. The selection first offers information on the cardiovascular effects of choline esters and the effects of choline esters on smooth muscles and secretions. Topics include actions of acetylcholine, physiological role of choline esters, and actions of cholinergic drugs on smooth muscles and secretions. The book also takes a look at the pharmacologic, toxicologic, and th.